The multiwavelength view of shocks in the fastest nova V1674 Her. Issue 4 (23rd March 2023) - Sokolovsky, K V; Johnson, T J; Buson, S; Jean, P; Cheung, C C; Mukai, K; Chomiuk, L; Aydi, E; Molina, B; Kawash, A; Linford, J D; Mioduszewski, A J; et al.
ABSTRACT: Classical novae are shock-powered multiwavelength transients triggered by a thermonuclear runaway on an accreting white dwarf. V1674 Her is the fastest nova ever recorded (time to declined by two magnitudes is t 2  = 1.1 d) that challenges our understanding of shock formation in novae. We investigate the physical mechanisms behind nova emission from GeV γ-rays to cm-band radio using coordinated Fermi -LAT, NuSTAR,   Swift, and VLA observations supported by optical photometry. Fermi -LAT detected short-lived (18 h) 0.1–100 GeV emission from V1674 Her that appeared 6 h after the eruption began; this was at a level of (1.6 ± 0.4) × 10 −6  photons cm −2  s −1 . Eleven days later, simultaneous NuSTAR and Swift X-ray observations revealed optically thin thermal plasma shock-heated to k T shock  = 4 keV. The lack of a detectable 6.7 keV Fe Kα emission suggests super-solar CNO abundances. The radio emission from V1674 Her was consistent with thermal emission at early times and synchrotron at late times. The radio spectrum steeply rising with frequency may be a result of either free-free absorption of synchrotron and thermal emission by unshocked outer regions of the nova shell or the Razin–Tsytovich effect attenuating synchrotron emission in dense plasma. The development of the shock inside the ejecta is unaffected by the extraordinarily rapid evolution and the intermediate polar host of this nova.